Polypharmacy, chronic kidney disease, and mortality among older adults: A prospective study of National Health and nutrition examination survey, 1999–2018 - Wang, Xiaowen; Yang, Chao; Jiang, Jie; Hu, Yonghua; Hao, Yuantao; Dong, Jia-Yi (Frontiers in Public Health, 2023)
Polypharmacy might contribute to a range of adverse outcomes, which could get worse in the elderly with chronic kidney disease (CKD). Evidence on polypharmacy, CKD, and mortality is scarce. We aimed to investigate the prospective association between polypharmacy, CKD and all-cause and cause-specific mortality in adults aged ≥65 years. A total of 13,513 adults from the National Health and Nutrition Examination Surveys were included, following up from 1999–2018 until December 31, 2019. The simultaneous use of ≥5 medications by one individual was defined as polypharmacy. Survey-weighted Cox proportional hazard models were used to estimate the hazard ratio (HRs) for mortality from all-cause, cardiovascular diseases (CVD), and cancer after adjusting for potential confounding factors. Among the elderly with CKD, we identified 3825 total deaths (1325 CVD and 714 cancer) during a median follow-up of 7.7 years. Participants with polypharmacy had a 27% (HR = 1.27 [1.15, 1.39]) and 39% (HR = 1.39 [1.19, 1.62]) higher risk of all-cause and CVD mortality, respectively, but not for cancer mortality. Compared with the elderly with no polypharmacy and no CKD, the corresponding HRs (95%CIs) were 1.04 (0.96, 1.14) for those with no polypharmacy but CKD, 1.24 (1.11, 1.39) for with polypharmacy but no CKD, and 1.34 (1.21, 1.49) for those with both polypharmacy and CKD. A similar pattern was detected for CVD mortality. Polypharmacy was associated with elevated risks of all-cause and CVD mortality among the elderly CKD patients. More evidence-based approaches should be promoted for the appropriate deprescribing in the older adults with CKD.